ASSOCIATION OF SHORT PERINEAL BODY LENGTH WITH OBSTETRIC ANAL SPHINCTER INJURIES IN PRIMIGRAVIDA UNDERGOING VAGINAL DELIVERY WITH EPISIOTOMY (Journal of Medical & Health Sciences Review, 2025)
Background: Obstetric anal sphincter injuries (OASI), remain a major complication of vaginal childbirth. A reduced perineal body length (PBL) suggested as an important risk factor for OASI.Objective: To determine whether short PBL is associated with a higher likelihood of OASI in primigravida delivering vaginally with episiotomy.Methods: This study was carried out in the Department of Obstetrics & Gynecology, Sir Ganga Ram Hospital, Lahore,from 1 April 2025 to 3 July 2025 . A total of 60 primigravida were recruited, divided into Group A with short PBL (≤3.0 cm, n=30) and Group B with longer PBL (>3.0 cm, n=30). Incidence of OASI was compared between groups, with additional stratified analyses performed for maternal age, body mass index (BMI), and neonatal birth weight. Data were analyzed using SPSS version 25.Results: Mean PBL was significantly shorter in Group A (2.8 ± 0.1 cm) than in Group B (3.5 ± 0.2 cm, p < 0.001). OASI occurred more frequently in women with short PBL—third-degree tears in 50% and fourth-degree in 23.3%—compared with 16.7% and 0% in Group B (p < 0.001). Subgroup analyses indicated that women aged ≤25 years, those with BMI ≥25 kg/m², and those delivering infants >3.5 kg were at greater risk of OASI when PBL was short.Conclusion: Shorter PBL is significantly associated with a higher incidence of OASI in primigravida women undergoing episiotomy-assisted vaginal delivery. Routine prenatal measurement of PBL, combined with consideration of maternal and fetal factors, could help in planning targeted preventive measures to reduce severe perineal trauma.